2010
DOI: 10.1128/iai.00613-10
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Heme Paradox: Heme Toxicity and Tolerance in Bacterial Pathogens

Abstract: Virtually all bacterial pathogens require iron to infect vertebrates. The most abundant source of iron within vertebrates is in the form of heme as a cofactor of hemoproteins. Many bacterial pathogens have elegant systems dedicated to the acquisition of heme from host hemoproteins. Once internalized, heme is either degraded to release free iron or used intact as a cofactor in catalases, cytochromes, and other bacterial hemoproteins. Paradoxically, the high redox potential of heme makes it a liability, as heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
281
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(292 citation statements)
references
References 137 publications
(187 reference statements)
2
281
0
5
Order By: Relevance
“…However, in contrast to other bacterial species, H. influenzae does not produce any siderophores by itself, but can utilize siderophores produced by other microorganisms for iron uptake (Morton et al, 2010). are known for storing heme at their surface and utilize it for virulence (Anzaldi and Skaar, 2010). H. influenzae outer membrane lipoprotein P4 was previously described to play role in hemin uptake and transport (Reidl and Mekalanos, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to other bacterial species, H. influenzae does not produce any siderophores by itself, but can utilize siderophores produced by other microorganisms for iron uptake (Morton et al, 2010). are known for storing heme at their surface and utilize it for virulence (Anzaldi and Skaar, 2010). H. influenzae outer membrane lipoprotein P4 was previously described to play role in hemin uptake and transport (Reidl and Mekalanos, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that haemin/haem is toxic at high concentration, and Porphyromonas spp. are highly susceptible to haem toxicity (Anzaldi & Skaar, 2010). We speculate that this haemin toxicity could be due to the release of free iron from haemin breakdown in the semi-CDMLK medium, which could result in oxidative stress that killed P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance to heme in bacteria has been attributed to a number of the following mechanisms: (i) regulation of heme uptake; (ii) heme export; (iii) heme sequestration, and (iv) heme degradation (11). Heme uptake in P. gingivalis is inextricably linked with iron metabolism and is up-regulated in growth under iron limitation (14).…”
mentioning
confidence: 99%
“…Because of the high redox potential of free heme, high concentrations can cause protein inactivation, fatty acid oxidization, and DNA damage through peroxidase-like and monooxygenase-like activities (11). Furthermore, the release of iron during heme degradation can cause oxidative damage by the production of hydroxyl radicals via the Fenton reaction (Fe 2ϩ ϩ H 2 O 2 3 Fe 3ϩ ϩ OH ⅐ ).…”
mentioning
confidence: 99%